Vivre la Ville en Écosse - Rosie Findlay, Tri Tran, William Findlay (dir.) (Presses universitaires François-Rabelais, 2005)
In the modem western world urbanisation has often been both the companion and corollary of industrialization and no more so than in Britain. Here the population changed dramatically during the long nineteenth century, transforming parts of England and Scotland into some of the most industrial and urban societies in the world. Scottish society was particularly affected by this process. The growth of towns or cities, and the radical overhaul of the balance of population between the rural and ur...